The Selected Works of George R. Lindsey : Operational Research, Strategic Studies, and Canadian Defence in the Cold War - Lindsey, George, 1920-2011 (Book collections on Project MUSE., 2019)
"Dr. George Lindsey (1920-2011), a leading Canadian defence scientist, gained widespread recognition in the western alliance during a government career that spanned nearly the whole of the Cold War. Trained as a scientist in nuclear physics, he became an operational researcher during the Second World War and a strategic analyst for the Canadian defence establishment in the postwar period. He played a key role in development modern capacities in both fields while defending Canadian interests on the front lines on Cold War military planning and preparations. He worked towards the cause of a more effective western alliance, influencing policy in such important areas as North American air defence, anti-submarine warfare and the militarization of space. In an active retirement, he then addressed the circumstances of the post-Cold War world. This book provides first access to a selection of unpublished and small-circulation documents that Lindsey produced during his long and interesting career. He left behind a collection of rich records that offer insight into his personal predilections and professional dispositions. A significant amount of his government work remains classified, but what information is open provides unique insights into postwar defence and policy formation in Canada. The writings provided here describe the work of an influential and largely unknown Canadian while also opening a window to the importance of governmental defence research to Canada's Cold War. Lindsey's records thus not only chronicle the noteworthy experiences of a pragmatic defence scientist, but also elucidate the priorities of the Canadian defence establishment during a significant period in world affairs."--